2017
DOI: 10.1002/ccd.26980
|View full text |Cite
|
Sign up to set email alerts
|

One‐year outcomes after successful chronic total occlusion percutaneous coronary intervention: The impact of dissection re‐entry techniques

Abstract: We aimed to determine clinical outcomes 1 year after successful chronic total occlusion (CTO) PCI and, in particular, whether use of dissection and re-entry strategies affects clinical outcomes. Hybrid approaches have increased the procedural success of CTO percutaneous coronary intervention (PCI) but longer-term outcomes are unknown, particularly in relation to dissection and re-entry techniques. Data were collected for consecutive CTO PCIs performed by hybrid-trained operators from 7 United Kingdom (UK) cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 25 publications
1
21
0
1
Order By: Relevance
“…In the current issue of the Journal, Wilson et al analyzed one‐year outcomes after 805 successful CTO percutaneous coronary intervention (PCIs). Subadventitial techniques were the final successful strategy in 375 (47%) cases . Consistent with previous reports, subadventitial techniques were utilized in more complex lesions (J‐CTO score 3.2 ± 1.2 vs. 1.8 ± 1.3, P = 0.001), and resulted in longer stent lengths and worse procedural efficiency metrics.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In the current issue of the Journal, Wilson et al analyzed one‐year outcomes after 805 successful CTO percutaneous coronary intervention (PCIs). Subadventitial techniques were the final successful strategy in 375 (47%) cases . Consistent with previous reports, subadventitial techniques were utilized in more complex lesions (J‐CTO score 3.2 ± 1.2 vs. 1.8 ± 1.3, P = 0.001), and resulted in longer stent lengths and worse procedural efficiency metrics.…”
supporting
confidence: 80%
“…However, there is the option of becoming an “antegrade only” CTO operator, by using antegrade but not retrograde dissection/re‐entry. The third question is “If during antegrade crossing attempts the guidewire enters the subintimal space should I continue antegrade wire escalation (e.g., using the parallel wire technique) or should I change to dissection/re‐entry?” This question remains unanswered: using dissection/re‐entry may improve the efficiency of the procedure, but may result in higher cost, longer stent length, side branch loss, and potentially higher restenosis rates (although the difference did not reach statistical significance in the study by Wilson et al ). On the other hand, continued wire crossing attempts could create a subintimal hematoma potentially hindering subsequent re‐entry attempts.…”
mentioning
confidence: 99%
“…Eleven studies with 4,260 patients were included, and low heterogeneity was found (I 2 = 26.50%, p = 0.192; Fig. 2D) [11,[14][15][16][17][18][19][20][21][22]24]. The data revealed significant differences between the two groups with regard to TVR (RR = 1.61, 95% CI: 1.29-2.01; Fig.…”
Section: Target Vessel Revascularizationmentioning
confidence: 88%
“…The CTO length was significantly longer in patients with subintimal DR techniques, when compared with conventional WE crossing (SMD: 0.64, 95% CI: 0.31-0.97, p < 0.001; I 2 = 83.4%, p < 0.001; Fig. 3D) [14,16,17,19,21].…”
Section: Cto Occlusion Length and J-cto Scorementioning
confidence: 93%
See 1 more Smart Citation